2006
DOI: 10.1161/circulationaha.106.177276
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Assessment of Coronary Artery Disease in the Cardiac Catheterization Laboratory

Abstract: Abstract-With advances in technology, the physiological assessment of coronary artery disease in patients in the catheterization laboratory has become increasingly important in both clinical and research applications, but this assessment has evolved without standard nomenclature or techniques of data acquisition and measurement. Some questions regarding the interpretation, application, and outcome related to the results also remain unanswered. Accordingly, this consensus statement was designed to provide the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
177
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 449 publications
(187 citation statements)
references
References 116 publications
4
177
0
2
Order By: Relevance
“…1 Abnormal CFR is often present in patients with essential hypertension despite the presence of angiographically normal coronary arteries and even in the absence of left ventricular (LV) hypertrophy. 2,3 Direct measurement of intracoronary flow velocity by using a Doppler guidewire constitutes the most reliable, though invasive, method for the evaluation of CFR.…”
Section: Introductionmentioning
confidence: 99%
“…1 Abnormal CFR is often present in patients with essential hypertension despite the presence of angiographically normal coronary arteries and even in the absence of left ventricular (LV) hypertrophy. 2,3 Direct measurement of intracoronary flow velocity by using a Doppler guidewire constitutes the most reliable, though invasive, method for the evaluation of CFR.…”
Section: Introductionmentioning
confidence: 99%
“…11 FFR was computed as the ratio of distal/aortic pressure during hyperaemia; FFR ≥0.75 was considered 'negative'. 2 …”
Section: Methodsmentioning
confidence: 99%
“…Assessment can be performed noninvasively (using myocardial perfusion scintigraphy; MPS) 1 or invasively during cardiac catheterisation using intracoronary derived haemodynamic indices. 2 Previous validation studies have shown good agreement (80 to 90%) between these parameters and the results of noninvasive stress tests. [3][4][5] Previously, we reported the final results of the ILIAS (Intermediate Lesions: Intracoronary flow Assessment versus 99m Tc-MIBI SPECT) study with one-year clinical follow-up.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Coronary vasodilatory reserve (or coronary flow reserve) is the ratio of hyperemic to basal average peak flow velocity. 57 Hyperemia is typically achieved with intracoronary adenosine, which dilates the microvasculature and is partially endothelial dependent. 35 Coronary vasodilatory reserve is commonly used for patients with coronary artery disease to evaluate the physiological significance of intermediate severity stenoses, serial stenoses and other lesions of unclear significance.…”
Section: Catheter Basedmentioning
confidence: 99%